Comovement amongst the demand for New Zealand tourism. (July 2020) - Vatsa, Puneet
Abstract: Tourism research is replete with applications of univariate time-series decomposition techniques: multivariate frameworks have been largely ignored. In this paper, we employ a common-feature-based, multivariate trend-cycle decomposition approach to examine common trends and common cycles amongst the demand for New Zealand tourism originating in Australia, China, the US, the UK, as well as other tourism-importing countries considered as one group: Others. Upon isolating trends and cycles in tourism demand from these countries, we find evidence of strong long-term comovement: they share one common trend. We also find evidence of short-term comovement, albeit to a lesser extent: four common cycles emerge; the cyclical patterns in tourism demand from Australia, China, the US, and Others are strongly correlated. Highlights: Comovement amongst international tourism demand for New Zealand is analyzed. Multivariate decomposition is employed to study common trends and common cycles. Common trends and common cycles exist in demand for New Zealand tourism. One common trend drives long-term international tourism demand. Cycles in international tourism demand are strongly and positively correlated.